2016
DOI: 10.1523/jneurosci.1370-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic Regulation of Schwann Cell Reprogramming in Peripheral Nerve Injury

Abstract: The rapid and dynamic transcriptional changes of Schwann cells in response to injury are critical to peripheral nerve repair, yet the epigenomic reprograming that leads to the induction of injury-activated genes has not been characterized. Polycomb Repressive Complex 2 (PRC2) catalyzes the trimethylation of lysine 27 of histone H3 (H3K27me3), which produces a transcriptionally repressive chromatin environment. We find that many promoters and/or gene bodies of injury-activated genes of mature rat nerves are occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 94 publications
4
108
0
Order By: Relevance
“…Therefore, we decided to examine regulation of Neuregulin1 ( Nrg1 ) type I, which is induced in Schwann cells within 24 hours after injury, and increases remyelination efficiency (Ronchi et al 2016; Stassart et al 2013). Interestingly, the ChIP-seq mapping of H3K27me3 in mature nerve (Ma et al 2016) indicated that transcription start sites of Nrg1 type I and III are occupied by this repressive histone mark (Figure 3A), and ChIP-qPCR assays showed a decrease in H3K27me3 in the type I promoter after injury (Figure 3B), showing a correlation between methylation dynamics of H3K27 and Nrg1 type I gene activation. Gene expression analysis of Eed cKO nerves, which display a Schwann cell-specific loss of H3K27me3 (Ma et al 2015), revealed derepression of Nrg1 type I in Eed cKO nerves at 2 months of age in the absence of injury (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we decided to examine regulation of Neuregulin1 ( Nrg1 ) type I, which is induced in Schwann cells within 24 hours after injury, and increases remyelination efficiency (Ronchi et al 2016; Stassart et al 2013). Interestingly, the ChIP-seq mapping of H3K27me3 in mature nerve (Ma et al 2016) indicated that transcription start sites of Nrg1 type I and III are occupied by this repressive histone mark (Figure 3A), and ChIP-qPCR assays showed a decrease in H3K27me3 in the type I promoter after injury (Figure 3B), showing a correlation between methylation dynamics of H3K27 and Nrg1 type I gene activation. Gene expression analysis of Eed cKO nerves, which display a Schwann cell-specific loss of H3K27me3 (Ma et al 2015), revealed derepression of Nrg1 type I in Eed cKO nerves at 2 months of age in the absence of injury (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Regenerating nerves initiate a program that includes myelin debris removal, axon regeneration and remyelination (Arthur-Farraj et al 2012; Jessen and Mirsky 2016). Since our previous studies showed precocious activation of injury genes in the Eed cKO (Ma et al 2016), we had anticipated that there may be accelerated regeneration. However, the ultrastructural analysis revealed that there were relatively fewer axons at the transverse sections 4 mm distal to the injury site in Eed cKO nerves compared to sections of control mice, which exhibited a substantial number of myelinated axons at 14 d after injury (Figure 1A, B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations